Endoscopic hemostasis in the ulcer gastro-duodenal hemorrhage, using high-frequency biological welding electro-ligature - Ya. P. Feleshtynskyi; S. O. Oparin; B. V. Sorokin; M. G. Boiarska; D. V. Lutsenko (Клінічна хірургія, 2020)
Objective. To improve the efficacy of endoscopic hemostasis for the ulcer gastro-duodenal hemorrhage, using high-frequency biological welding electro-ligature.